Development of a robust and efficient biogas processor for hydrogen production. Part 1: Modelling and simulation. (7th September 2017) - Montenegro Camacho, Y.S.; Bensaid, S.; Lorentzou, S.; Vlachos, N.; Pantoleontos, G.; Konstandopoulos, A.; Luneau, M.; Meunier, F.C.; Guilhaume, N.; Schuurman, Y.; Werzner, E.; Herrmann, A.; et al.
Abstract: The present work deals with the modelling and simulation of a biogas Demo-processor for green hydrogen production via Autothermal reforming (ATR) process aimed at covering a wide span of potential applications, from fuel cells feed up to the production of pure hydrogen. The biogas ATR unit is composed of a structured catalyst support close coupled to a wall-flow filter that retain soot particles that can be formed during the ATR reaction. Modelling and simulation (CFD and FEM) were carried out to select the innovative catalyst support with promising results for the fuel processor. 3D digital sample reconstruction was performed for the selection of the appropriate porous structures commercially available for the soot filtration and furthermore, 2D CFD analysis was also used to examine flow uniformity issues due to soot trap integration downstream to the ATR. Moreover, the inherent flexibility of the model performed allowed its application in the assessment of the Demonstration plant operating in real conditions. Besides, Aspen simulation has demonstrated that the ATR process is the most promising process to hydrogen production compared to other types of reforming process. Highlights: Production of hydrogen from ATR of biogas. The ATR unit is composed of a structured catalyst support close coupled to a wall-flow filter that retain soot particles. An efficiency plant equal to 65% (using S/C = 1.5 and O/C = 1.02) is achieved with an ATR process without using a PSA unit. Rotated cube cell is the most suitable catalyst support structure for the ATR of biogas.